Assessment of the quality and content of clinical practice guidelines for post-stroke rehabilitation of aphasia. Issue 31 (August 2019) - Wang, Yu; Li, Huijuan; Wei, Huiping; Xu, Xiaoyan; Jin, Pei; Wang, Zheng; Zhang, Shian; Yang, Luping
Abstract: Objectives: The purpose of this study was to evaluate the quality of guidelines for rehabilitation of post-stroke aphasia using the Appraisal of Guidelines for Research and Evaluation (AGREE-II) instrument and identify consistency of different guidelines. Methods: A systematic search was undertaken from inception to October 2018. Two reviewers independently screened all titles and abstracts, and assessed eligible guidelines using the AGREE-II. Agreement among reviewers was measured by using intra-class correlation coefficient (ICC). Results: From 5008 records screened, 8 guidelines met the inclusion criteria. The quality of guidelines was heterogeneous. Three guidelines were rated high (6.5) across; the highest rated domain was "scope and purpose" (median score 95.8%); the lowest rated domain was "rigor of development" (median score 67.2%). An overall high degree of agreement among reviewers to each domain was observed (ICC ranged from 0.60 to 0.99). The speech language therapy was recommended in 3 guidelines. Four guidelines described group treatment was beneficial for the continuum of care. However, other therapies for aphasia varied in the level of detail across guidelines. Conclusions: Our study indicated the quality of guidelines for post-stroke aphasia needed to be improved. Moreover, the treatment recommendations of aphasia existed discrepancy among the included guidelines. Therefore, it is suggested to pay more attention on the rigor of methodology and applicability during the process of the formulation of guideline. Future research should focus on the effectiveness, intensity, and duration of treatment measures. Abstract : Supplemental Digital Content is available in the text